The Evaluation of Appropriate Selection Learning Media at Junior High School - Hamsi Mansur; Agus Hadi Utama (Universitas Veteran Bangun Nusantara, 2021)
The appropriate selection of learning media can help the process of delivering messages from teachers to students become more effective. The selection of the right learning media requires the use of certain principles and criteria to be precise in choosing a learning medium because each learning medium should have different characteristics and specifications of usefulness. This study aims to conduct a summative evaluation of the appropriate selection of local wetland content learning media in junior high schools (SMP) in Banjarmasin. The appropriate selection of learning media will be evaluated with a summative model are all subjects containing local content of wetlands, such as in science & social subjects found by researchers in junior high schools in Banjarmasin through population methods and samples using purposive random sampling techniques as many as 5 junior high schools in Banjarmasin. Data analysis techniques in the evaluation of summative models are conducted descriptively-qualitatively using principle models and criteria used to evaluate the appropriateness of selection of local content learning media wetlands consisting of four components, namely: conformity with the material, conformity with student characteristics, conformity with the student's learning style, and conformity with supporting facilities. The results showed that the mapping appropriate of the selection of local wetland content learning media in junior high schools in Banjarmasin has met four criteria for appropriate choosing the right learning media with good categories. Recommendations of the results of the study evaluation of the appropriate selection of learning media can be tested in other schools to see the evaluation of the appropriate selection of online or remote learning media during the Covid-19 pandemic.